2008
DOI: 10.2350/07-05-0281.1
|View full text |Cite
|
Sign up to set email alerts
|

Study of an Ovarian Sclerosing Stromal Tumor Presenting as Vaginal Bleeding in a 7-Month-Old

Abstract: This communication describes the histological, immunohistochemical, ultrastructural, and cytogenetic study of an ovarian sclerosing stromal tumor resected from a 7-month-old girl who presented with vaginal bleeding. The tumor is very rare, its pathogenesis is not clear, and its hormonal activity has been subject to debate. In addition, it has been rarely seen in children and never in infants, with the youngest patient reported being 10 years of age. Histological study of the tumor showed a process of multinodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A previous study showed that SST might undergo a process of multinodular asynchronous growth followed by gradual loss of cells, hyalinization, and eventual transformation into corpora albicantia-like structures. 11 The histology of this tumor supports the aforementioned observation. It appears that this child’s tumor was at the end stage of the process with mainly corpora albicantia-like structures and scattered degenerative vacuolated cells.…”
Section: Case Discussionsupporting
confidence: 82%
“…A previous study showed that SST might undergo a process of multinodular asynchronous growth followed by gradual loss of cells, hyalinization, and eventual transformation into corpora albicantia-like structures. 11 The histology of this tumor supports the aforementioned observation. It appears that this child’s tumor was at the end stage of the process with mainly corpora albicantia-like structures and scattered degenerative vacuolated cells.…”
Section: Case Discussionsupporting
confidence: 82%
“…Consistent numerical chromosomal aberrations were described in 21 of 29 ovarian tumors in the thecoma-fibroma group, and 71.5% of the cases with chromosomal abnormalities had trisomy 12 (11). Trisomy 12 was found in 4 of 5 cases of SST studied indicating a close relationship to other ovarian stromal tumors (12)(13)(14). Likewise, trisomy 12 has been reported in 5 of 6 cases of ovarian JGCT examined (15,16); however, monosomy 22 has been found in adult-type granulosa cell tumor (17,18).…”
Section: Discussionmentioning
confidence: 78%
“…These tumors occur most frequently in the second and third decades of life; patients aged <30 years account for 78.8% of all cases. Since it was first described by Chalvardjian and Scully [3], around 200 cases have been reported [4,5,6,7,8]. SSTO occurs with similar frequency in the left and right ovaries; two bilateral cases have been reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a low-grade malignant SSTO has been reported in Portugal [5]. The youngest reported patient with an SSTO has been a 7-month-old girl with vaginal bleeding [6]. Another case report has described a huge SSTO weighing 10 kg in a 71-year-old postmenopausal woman [7].…”
Section: Discussionmentioning
confidence: 99%